Efficacy of Progressive Muscle Relaxation, Mental Imagery, and Phantom Exercise Training on Phantom Limb: A Randomized Controlled Trial - Brunelli, Stefano; Morone, Giovanni; Iosa, Marco; Ciotti, Cristina; De Giorgi, Roberto; Foti, Calogero; Traballesi, Marco (Archives of physical medicine and rehabilitation, 2015)
To evaluate the reduction in phantom pain and sensation with combined training of progressive muscle relaxation, mental imagery, and phantom exercises. Randomized controlled prospective trial with 2 parallel groups. Amputee unit of a rehabilitation hospital. Subjects with unilateral lower limb amputation (N=51) with phantom limb pain (PLP) and/or phantom limb sensation (PLS). The experimental group performed combined training of progressive muscle relaxation, mental imagery, and phantom exercises 2 times/wk for 4 weeks, whereas the control group had the same amount of physical therapy dedicated to the residual limb. No pharmacological intervention was initiated during the trial period. The Prosthesis Evaluation Questionnaire and the Brief Pain Inventory were used to evaluate changes over time in different aspects (intensity, rate, duration, and bother) of PLS and PLP. Blind evaluations were performed before and after treatment and after 1-month follow-up. The experimental group showed a significant decrease over time in all the Prosthesis Evaluation Questionnaire domains (in terms of both PLS and PLP; P<.04 for both) and the Brief Pain Inventory (P<.03). No statistically significant changes were observed in the control group. Between-group analyses showed a significant reduction in intensity (average and worst pain) and bother of PLP and rate and bother of PLS at follow-up evaluation, 1 month after the end of the treatment. Combined training of progressive muscle relaxation, mental imagery, and modified phantom exercises should be taken into account as a valuable technique to reduce phantom limb pain and sensation. [Display omitted] A photo taken during the experimental SAIPAN treatment (left). The improvement found in terms of reduction in phantom limb pain for the experimental group with respect to the control group depicted using as background a picture of the Saipan island (right) (the picture of the Saipan island was taken from a public repository: File:Saipan-Forbidden-Island.jpg from https://commons.wikimedia.org/wiki/Main_Page Wikimedia Commons') •A combination of progressive muscle relaxation, mental imagery, and modified phantom exercise training (the SAIPAN protocol) was effective in reducing the intensity, rate, and bother of phantom limb pain and sensation.•The benefits of SAIPAN treatment are significant 1 month after the end of treatment.•Because of cumulative effects, treatment should be continued throughout the planned 4 weeks despite possible small effects in the first sessions.